Accounting Information System Analysis on Sales Transactions: Analisis Sistem Informasi Akuntansi atas Transaksi Penjualan - Bardina , Abidah Garizah; Nurasik, Nurasik (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Accounting information systems play a crucial role in ensuring the accuracy and efficiency of company sales transactions. Specific Background: In practice, some companies still face challenges in implementing effective accounting information systems that align with internal control principles. Gap: Limited studies analyze the structure and implementation of sales accounting information systems in medium-scale enterprises. Aims: This study aims to analyze the accounting information system and internal control mechanisms of sales transactions at PT. Daya Anugerah Mandiri Manado. Results: The findings reveal that the company’s accounting system has been properly implemented and effectively supports transaction accuracy, although improvements are needed in documentation and data validation. Novelty: The study highlights the practical evaluation of internal control in the context of a regional sales enterprise. Implications: The results contribute to developing more efficient and reliable accounting systems in corporate environments. Highlights:• Evaluation of accounting information systems in a regional company• Internal control supports transaction accuracy and efficiency• Manual processes still dominate and need digital integration Keywords: Accounting Information System, Sales Transaction, Internal Control, System Evaluation, Efficiency